Policy directions for health in the 1980s - Cariño, Ledivina V. (1981)
The Philippine health situation at the start of the 1980s is characterized by achievements due to the institution and/or intensification of programs stressing the concept of accessibility and decentralization. These programs include the Restructured Rural Health Care Delivery System, the Medical Care Program, Rural Health Practice Program, Community Medicine Focus of Medical and Nursing Schools, Community-Based Health Programs and a newer development, the Primary Health Care. But despite these programs, problems on health per se and those of access to health resources still exist. The agenda for health in the 1980s should therefore consider these facts. It should also be made within the context of the nations's total economic, social, and political situation. The health policy should specifically aim at the promotion of health and the prevention of disease, the provision of adequate health care particularly to the poor, recognition and support to indigenous systems, and preparations to face problems of health and access brought about by increasing industrialization and urbanization. Many of these policy directions are already included in the present programs. They must be reiterated and underscored and new policies must be pointed out to complement them.
Keywords: Community health services; Medical care; Health care delivery; Rural Health Care Delivery System